SOLAR CABINET DRYER INTEGERATED WITH HEAT STORAGE UNIT FOR THE METREOLOGICAL CONDITION OF OMAN - JOSEPHINE SELVI.N; BASKAR.G; ARUNA SINGH (International Journal of Pharma and Bio Sciences, 2016)
The date is. the major. agricultural crop. in Sultanate of Oman. This work benefits. the local community the date farmers. in particular, where. date cultivation is. an important part of. the economy. Solar energy is one. of the most. abundantly available. renewable energy on the earth. It is a clean. energy that is environment friendly. and extremely cost effective, when considering. the life time output of the solar energy producing system. Solar cabinet. dryer designed and. fabricated by the corresponding author was used for the study. Design of solar. cabinet dryer was available elsewhere. The performance analysis of the dryer was done by comparing the quality of date dried from. solar dryer with open sun drying. The time taken to reduce the moisture content of dates from 49.02 % to 35.21% was. 2 days (24 hours) for cabinet dryer and 4 to 5 days (48 hours) . for open sun drying. under test condition. The experiment is. carried out for nearly. two days from 7 am. to 7pm. The thermal. efficiency of solar. dryer obtained for. the month of August. 2015 in sultanate of Oman is. 26%. The quality of .date dried using. the cabinet dryer. was encouraging. Browning of dates was reduced compared to the sun dried one. Similarly the original soft texture was. maintained, also the cabinet dried. date was free from. dust and .termites. Skin separation. in the final dried. product was less. Hence solar cabinet drier. is recommended. for drying agricultural. products in rural. areas of Sultanate of Oman. where electricity. is a major. constraint.